LEGAL FOUNDATIONS OF COMBATING CORRUPTION IN UZBEKISTAN - Bahtiyarova Zuhra ,; K.G. Mamatkulov, (TADQIQOTLAR, 2026)
This article provides a comprehensive theoretical and legal analysis of the legal foundations for combating corruption in the Republic of Uzbekistan. It examines the essence of corruption as a complex socio-legal phenomenon that undermines the rule of law, weakens public trust in state institutions, and hinders sustainable economic and social development. Based on the analysis of national legislation and international legal instruments, the study identifies the system of normative legal acts that form the legal basis of anti-corruption activity. Particular attention is paid to the constitutional principles, the Law of the Republic of Uzbekistan “On Combating Corruption,” the role of the Anti-Corruption Agency, and the importance of international cooperation within the framework of the United Nations Convention against Corruption. The study formulates scientifically grounded conclusions and proposals aimed at strengthening preventive mechanisms, enhancing legal awareness, and ensuring transparency and accountability in the activities of state bodies.